Culture and Social Ethics of Online Drivers (Phenomenological Study of Partner Behavior of Grab in the City of Makassar): Budaya dan Etika Sosial Pengemudi Online (Studi Fenomenologis Perilaku Mitra Grab di Kota Makassar) - Ibrahim Sudirman; Shermina Oruh; Andi Agustang (Jurnal Kolaboratif Sains, 2024)
This research aims to elaborate on and explore information regarding the Culture and Social Ethics of Online Transportation Drivers in the city of Makassar, as well as the triggering and supporting factors in the formation of these social behaviors. Another objective is to reveal and describe the behaviors and positive values inherent in workers or Transportation Partners, especially those affiliated with Grab and Gojek. The research method employed is qualitative with a phenomenological descriptive approach. Phenomenological approach is a qualitative research method that aims to reveal shared meanings that constitute the essential substance of a consciously and individually experienced phenomenon by a group of individuals. Phenomenology reconstructs the phenomenon and its meaning for individuals through subject interviews. Phenomenological studies argue that each subject experiences a phenomenon with conscious conditions, so this approach aims to uncover the individual's deepest awareness of the experience in an event. The results of the research indicate that the Culture and Social Ethics of Drivers or Transportation Partners are reflected in attitudes or social behaviors, including the growth of social sensitivity and social solidarity. Solidarity among drivers is built on the basis of humanity and responsibility for living and working together, such as mutual assistance, cooperation, or mutual help on the road. The formation of social communities also results from the commonality of profession and fate to survive in meeting the necessities of life. Solidarity among drivers becomes a social unity in the form of a social group driven by unity through social attachment to fellow transportation partners.